Слідами «Львівського погрому» Джона-Пола Химки - Рябенко, С. (Український визвольний рух, 2013)
Рецензія на: John-Paul Himka. The Lviv Pogrom of 1941: The Germans, Ukrainian Nationalists, and the Carnival Crowd // Canadian Slavonic Papers / Revue canadienne des slavistes. — 2011. — Vol. LIII. — № 2—3—4. — P. 209—243. Review: John-Paul Himka. The Lviv Pogrom of 1941: The Germans, Ukrainian Nationalists, and the Carnival Crowd // Canadian Slavonic Papers / Revue canadienne des slavistes. — 2011. — Vol. LIII. — № 2—3— 4. — P. 209—243.